Implementasi Program Corporate Social Responsibility - Samsidik Samsidik; Cepi Nurhayana (Publikasi Indonesia, 2022)
This study aims to determine the implementation of the Corporate Social Responsibility Program (Case Study at PT. Bumi Duta Perada). This study uses a library research method, where the study is based on expert opinions about the Corporate Social Responsibility Program, business ethics and its role in the company. This Corporate Social Responsibility program can be carried out in all aspects. Maintaining mutual trust in cooperation will have a major impact on the company's reputation, of course this will not provide immediate benefits, but this is a form of long-term investment for all elements in the business circle. internal or external aspects, the expected progress or achievement of the company cannot be separated from the influence of Human Resources, if the human resources are poor then the results obtained from the company will be comparable to the existing human resources in the company, so that when the Corporate Social Responsibility in a company will be maximized if the influential aspects are carried out properly, the results obtained from the company will be maximized.